2022
DOI: 10.26464/epp2022003
|View full text |Cite
|
Sign up to set email alerts
|

Neutralized Solar Energetic Particles for SEP Forecasting: Feasibility Study of an Innovative Technique for Space Weather Applications

Abstract: Energetic neutral atoms (ENAs) are produced by the neutralization of energetic ions formed by shock-accelerated gradual solar energetic particle events (SEP). These high-energy ENAs (HENAs) can reach the Earth earlier than the associated SEPs and provide information about the SEPs at the lower corona. The HENA properties observed at Earth depend on the properties of the coronal mass ejection (CME)-driven shocks that accelerate the SEPs. With a model of HENA production in a shock-accelerated SEP event, we semi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 13 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…The first ENA simulation was done by Wang et al (2014), who simulated a CME-driven shock from a side-on orientation and suggested that the observed flux in Mewaldt et al (2009) is consistent with ENA production at a CME-driven shock. More recently, Wang et al (2014Wang et al ( , 2022 examined a variety cases with different CME speeds, open angles, and CME propagation directions. They also examined the effect of solar wind density variation near the Sun on the production of ENAs.…”
Section: Enas From Cme-driven Shocksmentioning
confidence: 99%
See 1 more Smart Citation
“…The first ENA simulation was done by Wang et al (2014), who simulated a CME-driven shock from a side-on orientation and suggested that the observed flux in Mewaldt et al (2009) is consistent with ENA production at a CME-driven shock. More recently, Wang et al (2014Wang et al ( , 2022 examined a variety cases with different CME speeds, open angles, and CME propagation directions. They also examined the effect of solar wind density variation near the Sun on the production of ENAs.…”
Section: Enas From Cme-driven Shocksmentioning
confidence: 99%
“…The energy ranges for these cross sections are also limited. Following Wang et al (2022), we have extended them to a larger energy range whenever necessary. It should be noted that, as in Wang et al (2014), we ignore charge exchanges by other ions (He + , N 5+ , etc.…”
Section: Orcid Idsmentioning
confidence: 99%
“…As in W14, we presume the center of the shock has a trajectory in the ecliptic plane and is perpendicular to the Earth-Sun line. The shape of the shocked region is conical, with a spherical cap at the position of the shock, and a spherical indent at 1.5 R e (see Figure 1 of Wang et al 2022). The full opening angle of the cone is 60°, again, as in W14.…”
Section: Shock Model Overviewmentioning
confidence: 87%
“…where Θ(ξ) is the Heaviside step function; r is the heliocentric distance and is equal to + + x y z 2 2 2 ; r s is the shock's location and is equal to r s,0 + u s t; the initial shock location r s,0 is equal to 1.5 R e , as in W14; f d is the downstream distribution and is simply equal to f 0 ; n(r s ) is the solar wind density at the location of the shock and is calculated using Equation (2) in W14; n 0 is the density at which the shock simulations were run (see Section 3); and the cone angle of the shock is defined by y = y r cos . In the above, we have used the same coordinate system as Figure 1 of Wang et al (2022), where the Sun is at the origin, the observer is at 1 au in the positive x-direction, and the CME's trajectory is in the positive y-direction.…”
Section: The Accelerated Proton Distributionmentioning
confidence: 99%
See 1 more Smart Citation